2015
DOI: 10.1007/s10973-015-4927-z
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition and combustion of n-hexane spray in subcritical and supercritical environments

Abstract: In this study, processes of a liquid fuel spray ignition and heat release during its combustion were under investigation. The purpose of this study was to elucidate whether the ignition properties and heat release process of a liquid fuel injected into the environments of parameters exceeding its critical values differ from those obtained for subcritical regimes. Therefore, the fuel was injected into the environments of parameters below, around and above its critical values. The ignition and combustion process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Based on this analysis, it can be concluded that the improvement of ecological and economic parameters of combustion engines depends primarily on the correct execution of the combustion process -depending largely on the activation energy and on the presence of a catalyst increasing the rate of chemical reactions [7,8]. Therefore, it is proposed that this internal catalyst should be used as an outer surface for selected combustion chamber elements.…”
Section: Internal Catalysts Application Possibilitiesmentioning
confidence: 99%
“…Based on this analysis, it can be concluded that the improvement of ecological and economic parameters of combustion engines depends primarily on the correct execution of the combustion process -depending largely on the activation energy and on the presence of a catalyst increasing the rate of chemical reactions [7,8]. Therefore, it is proposed that this internal catalyst should be used as an outer surface for selected combustion chamber elements.…”
Section: Internal Catalysts Application Possibilitiesmentioning
confidence: 99%
“…However, despite the introduction of advanced technical solutions for the engines themselves as well as the exhaust aftertreatment systems, it is not possible to completely eliminate the problem of emissions from the powertrains with combustion engines. Consequently, interest in electric vehicles has increased over the past 20 years [3]. The pure electric drive for vehicles has the advantage that the vehicle does not emit toxic components or CO 2 in the area where it is used.…”
Section: Introductionmentioning
confidence: 99%
“…in general, the overall volume-time characteristics of the fuel injection process significantly affect the heat release and, consequently, the engine performance, as well as the contents of harmful substances in the exhaust gas, including solid particles (mainly soot), and the noise generated by the engine in operation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%